A QUALITATIVE EXPLORATION OF BARRIERS AND FACILITATORS TO WEIGHT MANAGEMENT AMONG STUDENT WITH OBESITY IN PEMBANGUNAN NASIONAL VETERAN JAKARTA UNIVERSITY - Joselin, Angelia; Octaria, Yessi Crosita (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2024)
Background: Obesity is one of the problems that has a significant increase every year. If obesity is increasing, especially in the younger generation, it will have a bad impact. One of them is a decrease in productivity and adding to the burden on the country's economy in the long run. Therefore, adolescents or young adults with obesity, are required to carry out weight management programs to prevent the adverse effects caused by obesity. Objectives: This study was conducted to explore the supporting and inhibiting factors in conducting a weight management program and how these factors, both supporting and inhibiting, relate to each other. Methods: This research was conducted by qualitative methods. Data collection in this study was carried out by primary informant interviews, focus group discussions, and supporting informant interviews. Results: In this study, it was found that the supporting factors are oneself (daily habits, perceptions of obesity, and access to food) and the support of people around (moral support and provided facilities by parents). While the inhibiting factors are oneself (daily habits) and obstacles to people around (obstacles to asking for facilities, coercion from friends to eat, lecture agendas, and perceptions about obesity). The interaction between supporting and inhibiting factors is different in each individual. There are factors that support one student group but become an obstacle for other students. Conclusions: Supporting factors and inhibiting factors in carrying out a weight loss program are oneself and the surrounding environment, where between factors there are differences in impact on each individual. Keywords: Obesity, Weight Management, Facilitators, Barriers, Theory of Planned Behaviour (TPB)